Relations Between the Holy See and Lithuania: A 100-Year History - Haroldas Šinkūnas; Indrė Isokaitė-Valužė (Acta Universitatis Lodziensis Folia Iuridica)
The Article provides the analysis of the relations of the Holy See and the Republic of Lithuania from the beginning of the State’s independence until the current period. At the outset, the authors give an overview of different stages and key legal issues of the development of the said relations. Further, the research deals with typical provisions and specific features of a concordat as an international agreement. The following part of the article is devoted to the analysis of the provisions of current four agreements between the Holy See and Lithuania, adding comparison with the treaties concluded by the Holy See with other two Baltic States, namely Latvia and Estonia. The research focuses on key legal issues of the cooperation between the Holy See and Lithuania with minor aspects of the intersection of the historical, political, international, and religious context. The authors conclude that in the complex international political landscape, the Holy See has remained one of the most credible partners for Lithuania and a moral authority for the nation, dominated by Catholics. The recognition of Lithuania as a State shortly after its Independence Declaration of 1918 as well as non-recognition of its 50-year occupation significantly contributed to the restoration of the State’s independence in 1990. Although the reestablishment of the independent State of Lithuania being based on the continuation of the State’s identity opened door for securing the validity of the Concordat concluded by the Holy See and the Republic of Lithuania in 1927, it was no longer capable of reflecting new realities, and new fundamental changes required the conclusion of new treaties between the parties. In 2000, the Agreement concerning Juridical Aspects of the Relations between the Catholic Church and the State, the Agreement on Cooperation in Education and Culture, and the Agreement concerning the Pastoral Care of Catholics Serving in the Army were concluded between the Holy See and the Republic of Lithuania, while in 2012, the Agreement on the Recognition of Qualifications Concerning Higher Education occurred. These bilateral agreements reflect typical provisions of concordats arising from their unique nature of combining both political (legal) and ecclesiastical matters and securing autonomy of both parties: they regulate the legal status of the Catholic Church and numerous issues, encompassing institutional matters, religious freedom, religious education, family life, cultural heritage, pastoral care, and many others. These provisions are also similar in the agreements concluded by the Holy See and other two Baltic States, all having no state religion. However, the treaties of the Holy See concluded with Lithuania and Latvia have more common and more elaborated provisions than the agreement with Estonia, while some issues are relevant and, therefore, regulated in respect of merely a particular state.